Meta-Analysis: The Impact of Product, Price, Place, and Promotion on Patient Satisfaction - Hafida, Salsabilla Luthfiana Ayu; Hastuti, Rela; Murti, Bhisma; Handayani, Anggun Fitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: A component of effective health care is measuring patient satisfaction. Satisfaction helps in the evaluation of health services from the patient's perspective. In order to compete globally, hospitals need to consider marketing strategies that emphasize understanding customer needs, wants and demands. One of the most common and widely applied marketing concepts in this context is the marketing mix, which includes four main elements, namely product, place, promotion and price. This research aims to estimate the magnitude of the influence of the marketing mix (4P) which includes product, price, place and promotion on patient satisfaction. Subjects and Method: Meta-analysis studies with PICO research questions. Population = general patients. Intervention = high product quality, high promotion, long distance and high price. Comparison = low product quality, lack of promotion, close distance to facilities, and low price. Outcome= Patient satisfaction. Data obtained from Google Scholar, Pubmed, Scopus and ScienceDirect, with the keywords